Expression, purification and characterization of halophilic protease Pph_Pro1 cloned from Pseudoalteromonas phenolica - Johnson, Jervian; Yang, Yung Hun; Lee, Doo Geun; Yoon, Jeong Jun; Choi, Kwon Young (Protein Expression and Purification, 2018)
In this study, protease Pph_Pro1 from Pseudoalteromonas phenolica, possessing extracellular proteolytic activity and salt tolerance, was investigated for cloning, expression, and purification purposes. Through optimization, it was determined that optimum soluble recombinant expression was achieved when Pph_Pro1 was co-expressed with the pTf16 vector chaperone in LB medium supplemented with CaCl2. Pph_Pro1 was purified using osmotic shock and immobilized metal-affinity chromatography (IMAC). Isolated Pph_Pro1 activity was measured as 0.44 U/mg using casein as a substrate. Interestingly, Pph_Pro1 displayed halophilic, alkaliphilic, and unexpected thermostable properties. Furthermore, it was resistant to several hydrophilic and hydrophobic organic solvents. Substrate specificity and kinetic values such as Km and Vmax were determined with casein, bovine serum albumin (BSA), and algal waste protein as substrates, indicating that the Pph_Pro1 protease enzyme had a greater affinity for casein. Based on the remarkable characteristics of this Pph_Pro1 protease enzyme, it can potentially be utilized in many biotechnological industries.
Keywords: Algal Proteins; Bacterial Proteins; Calcium Chloride; Caseins; Chromatography, Affinity; Cloning, Molecular; Culture Media; Enzyme Assays; Enzyme Stability; Escherichia coli; Gene Expression; Genetic Vectors; Kinetics; Molecular Chaperones; Peptide Hydrolases; Proteolysis; Pseudoalteromonas; Recombinant Fusion Proteins; Salinity; Salt Tolerance; Serum Albumin, Bovine; Substrate Specificity; Casein hydrolysis; Chaperone; Halophilic microorganism; Protease; Proteolysis; Pseudoalteromonas phenolica